Actinobacillus actinomycetemcomitans lipopolysaccharide induces interleukin-6 expression through multiple mitogen-activated protein kinase pathways in periodontal ligament fibroblasts - Patil, C.; Rossa, C.; Kirkwood, K. L. (Blackwell Publishing, 2006)
Actinobacillus actinomycetemcomitans plays a major role in the pathogenesis of aggressive periodontitis. Lipopolysaccharide (LPS) derived from A. actinomycetemcomitans is a key factor in inflammatory cytokine generation within periodontal tissues. In this study, we identify major mitogen-activated protein kinase (MAPK) signaling pathways induced by A. actinomycetemcomitans LPS, Escherichia coli LPS and interleukin-1 beta (IL-1 beta) in a murine periodontal ligament (mPDL) fibroblast cell line. Immunoblot analysis was used to assess the phosphorylated forms of p38, extracellular-regulated kinase (ERK) and c-jun N-terminal kinase (JNK) MAPK following stimulation with A. actinomycetemcomitans LPS, E. coli LPS and IL-1 beta. IL-6 mRNA induction was detected via reverse transcription-polymerase chain reaction, while protein levels were quantified via enzyme-linked immunosorbent assays (ELISA). We utilized biochemical inhibitors of p38, ERK and JNK MAPK to identify the MAPK signaling pathways needed for IL-6 expression. Additional use of stable mPDL cell lines containing dominant negative mutant constructs of MAPK kinase-3 and -6 (MKK-3/6) and p38 null mutant mouse embryonic fibroblast (MEF) cells were used to substantiate the biochemical inhibitor data. Blocking p38 MAPK with SB203580 reduced the induction of IL-6 mRNA by A. actinomycetemcomitans LPS, E. coli LPS and IL-1 beta by > 70%, > 95% and similar to 60%, respectively. IL-6 ELISA indicated that blocking p38 MAPK reduced the IL-6 protein levels induced by A. actinomycetemcomitans LPS, E. coli LPS and IL-1 beta by similar to 60%, similar to 50% and similar to 70%, respectively. All MAPK inhibitors significantly reduced the IL-6 protein levels induced by A. actinomycetemcomitans LPS, E. coli LPS and IL-1 beta whereas only p38 inhibitors consistently reduced the A. actinomycetemcomitans LPS, E. coli LPS and IL-1 beta induction of IL-6 mRNA steady-state levels. The contribution of p38 MAPK LPS-induced IL-6 expression was confirmed using MKK-3/6 dominant negative stable mPDL cell lines. Wild-type and p38 alpha(-/-) MEF cells provided additional evidence to support the role of p38 alpha MAPK in A. actinomycetemcomitans LPS-stimulated IL-6. Our results indicate that induction of IL-6 by E. coli LPS, IL-1 beta and A. actinomycetemcomitans LPS requires signaling through MKK-3-p38 alpha ERK, JNK and p38 MAPK in mPDL cells.
Keywords: Actinobacillus actinomycetemcomitans; interleukin-6; LPS; MAPkinases; periodontal disease; periodontal ligament fibroblast